Primary health care of women: an educational-preventive approach to combat cancer cervical - Cardoso do Prado, Mara Rúbia Maciel; Silveira, Carmen Lúcia Paiva (Revista de Enfermagem UFPE on line, 2010)
ABSTRACT Objective: analyzing the acceptance of women in the Polyclinic Dr. Evaristo Pereira de Carvalho for performing the Pap examination, linked to SUS (Health Unique System), in Muriaé, Minas Gerais. Method: quantitative research, which had the object of the study 76 women. The criteria for inclusion in the study were: having a cervical smear with the nurse researcher, participation in the waiting room, accompanied by a period of one year. It was used for the data collection a questionnaire administered to participants after the educational lectures in the waiting room. The study was approved by the Ethics Committee on Faminas Muriaé under protocol number 007/2008. Results: we could see the influence of the practices of health education in the accession of women to take preventive and return in range for carrying out further tests. Final considerations: There was the importance of educational practices that affected women, which had the positive consequence of the accession of all the Pap test. Descriptors: education’s health; primary health care; women's health; papanicolau exam. RESUMO Objetivo: analisar a adesão ao exame Papanicolau das mulheres da Policlínica Dr. Evaristo Pereira de Carvalho, em Muriaé, Minas Gerais, vinculada ao Sistema Único de Saúde (SUS). Método: pesquisa quantitativa, que teve como objeto do estudo 76 mulheres. Os critérios para inclusão no estudo foram: realização do preventivo com a enfermeira pesquisadora; participação na sala de espera, acompanhamento por um período de um ano. Foi utilizado como instrumento de coleta de dados um questionário aplicado às participantes após as palestras educativas na sala de espera. O estudo foi aprovado pelo Comitê de Ética na FAMINAS de Muriaé sob o protocolo de aprovação 007/2008. Resultados: pôde-se verificar a influência das práticas de educação em saúde na adesão das mulheres ao exame preventivo, e o retorno no intervalo indicado para a realização de novos exames. Conclusão: observou-se a importância das práticas educativas que sensibilizaram as mulheres, as quais tiveram como conseqüência positiva a adesão de todas ao exame de Papanicolau. Descritores: educação em saúde; atenção primária à saúde; saúde da mulher; exame papanicolau. RESUMEN Objetivo: examinar la adhesión a la Policlínica de Papanicolaou de la Mujer Dr. Evaristo Pereira de Carvalho, en Muriaé, Minas Gerais, vinculada a la del SUS. Método: la investigación cuantitativa, que tenía por objeto el estudio de 76 mujeres. Los criterios para su inclusión en el estudio fueron: tener una citología cervical con la enfermera investigadora, la participación en la sala de espera, acompañado por un período de un año. Se utilizó como un instrumento de recolección de datos de un cuestionario aplicado a los participantes después de las charlas educativas en la sala de espera. El estudio fue aprobado por el Comité de Ética en Muriaé hambre bajo la aprobación del protocolo 007/2008. Resultados: se pudo ver la influencia de estas conferencias en el cumplimiento de estas mujeres para que tomen medidas preventivas cuando regresaban de un intervalo de aproximadamente un año para llevar a cabo exames. Consideraciones finales: nuevo destacó la importancia de las prácticas educativas que las mujeres afectadas, que tuvo la consecuencia positiva de la adhesión de todas las pruebas de Papanicolaou. Descriptores: educación salud; atención primaria de salud; salud de la mujer; prevención de cáncer de cuello uterino.